Impact of Reduction in Myeloid‐derived Suppressor Cells by Wilms’ Tumor 1‐targeted Dendritic Cell Vaccines on Clinical Outcomes in Acute Leukemia Patients - Masahiro Ogasawara; Mamiko Miyashita; Yuka Yamagishi; Shuichi Ota (eJHaem)
ABSTRACT Background Myeloid‐derived suppressor cells (MDSCs) play a critical role in immunotherapy. Methods We investigated the effects of the Wilms' tumor 1 (WT1) peptide‐loaded dendritic cell (DC) vaccination on MDSCs in patients with acute leukemia. Results WT1‐DC vaccination reduced MDSCs and enhanced WT1‐specific immunity. In complete remission patients, MDSC reduction was accompanied by decreased arginase 1 and indoleamine 2,3‐dioxygenase levels and increased interleukin (IL)‐12 and interferon‐γ levels in plasma. Conversely, patients with disease progression showed increased IL‐10 and transforming growth factor‐β1. Reduced MDSCs were correlated with WT1‐specific immune activation and associated with longer survival. Conclusion These findings indicate that WT1‐DC vaccination suppresses MDSCs and improves clinical outcomes. Clinical Trial Registration This study is registered with the University Hospital Medical Information Network (UMIN) in Japan (Registration ID: UMIN000027279).